2019
DOI: 10.1097/aud.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Electric and Acoustic Stimulation Influences Speech Perception in Ipsilateral EAS Users

Abstract: Objectives: The aim of this study was to determine electric-acoustic masking in cochlear implant users with ipsilateral residual hearing and different electrode insertion depths and to investigate the influence on speech reception. The effects of different fitting strategies—meet, overlap, and a newly developed masking adjusted fitting (UNMASKfit)—on speech reception are compared. If electric-acoustic masking has a detrimental effect on speech reception, the individualized UNMASKfit map might be abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
(109 reference statements)
4
26
0
Order By: Relevance
“…The criteria for candidacy of implantable technology (Kirkby-Strachan and Que-Hee 2016; Irving et al 2014), which are based on the benefit observed by using acoustical devices, are sometimes insufficient. New findings with electro-acoustic stimulation (Imsiecke et al 2019) suggest that this technology might benefit patients with a high degree of speech-intelligibility related deficits, i.e. with HL HF > 50 dB HL as shown here.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The criteria for candidacy of implantable technology (Kirkby-Strachan and Que-Hee 2016; Irving et al 2014), which are based on the benefit observed by using acoustical devices, are sometimes insufficient. New findings with electro-acoustic stimulation (Imsiecke et al 2019) suggest that this technology might benefit patients with a high degree of speech-intelligibility related deficits, i.e. with HL HF > 50 dB HL as shown here.…”
Section: Discussionsupporting
confidence: 51%
“…with HL HF > 50 dB HL as shown here. Despite the detrimental effect of the interaction between electrical and acoustical stimulations, Imsiecke et al (2019) showed that the use of masking-adjusted fittings with the aim of reducing electric-on acoustic masking strength was beneficial for speech intelligibility even in the cases with good residual hearing. Therefore, the present characterization into auditory profiles might support a revision of the candidacy of implantable devices that might include less severe hearing losses at high frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the current study extended the bandwidth through an additional phantom channel which allowed the use of the same electrode-frequency allocation for all other CI channels. Therefore, the subjects of the current study may have been less influenced by acclimatization effects when using the extended and the restricted bandwidth in comparison to the subjects tested in the previous studies of Imsiecke et al (2020), Karsten et al (2013), and Reiss et al (2012). For this reason, we observed significant differences when extending the bandwidth using EPS.…”
Section: Discussionmentioning
confidence: 60%
“…Krüger et al (2017) showed that EAS masking increases with decreasing distance between the stimulation site of electric and acoustic stimulation in the cochlea, the so-called electric-acoustic frequency difference (EAFD). Imsiecke et al (2020) showed a correlation between psychoacoustic EAS masking and the deterioration in speech perception for EAS subjects fitted with a spectral overlap. Moreover, Saoji et al (2018) observed that phantom stimulation increases masking between electric and acoustic stimulation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation